EFEKTIFITAS PERAWATAN INFUS UMBILIKAL TERHADAP TIMBULNYA FLEBITIS PADA NEONATUS - Dina Indrati; D Sulistyowati; Remilda Armika Vianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Background : The things to do to prevent from the appearance of phlebitis are the changing of the wound covering sterilized dressing, the evaluation to the appearance of phlebitis, the changing of the insertion area at every 48-72 hours, and the use of new catheterization set. The neonatus catheterization is usually placed at umbilical vein. As a result the neonatus with umbilical catheterization is easy to get phlebitis if the catheterization isn’t appropriate. Objective : To understand the difference of the effectiveness of the umbilical intravenous catheterization nursing using dry sterilized dressing and covered antiseptic sterilized dressing concerned with the appearance of phlebitis on neonatus. Method : The study was a queasy-experiment with post-test only design; used to examine the difference  of effectiveness of the umbilical intravenous catheterization nursing using dry sterilized dressing and covered antiseptic sterilized dressing concerned with the appearance of phlebitis on neonatus. Result : The result showed that there was no significant differences in the use of the dry sterilized dressing nursing and the covered antiseptic sterilized one as shown by p value score as much as 0,663 >0,05 with the fact that the Low Birth-weight babies and premature ones  tend to  have phlebitis. Conclusion : There is no significant differences in the umbilical catheterization nursing between use of the dry sterilized dressing and the covered antiseptic sterilized one concerned with the appearance of phlebitis but there is a tendency that the low birth-weight neonatus and premature ones  will have phlebitis more easily.